Selective depletion of regulatory T cells enhances the immunogenicity of a recombinant-based vaccine against Sporothrix spp - Batista-Duharte, Alexander; Téllez-Martínez, Damiana; Portuondo, Deivys Leandro; Carlos, Iracilda Zeppone (Frontiers in Cellular and Infection Microbiology, 2023)
Regulatory T (Treg) cells have been shown to limit vaccine-induced T-cells responses in different models. To learn more about the specific function of Tregs during vaccination, we used the DEREG mice, in which only Foxp3(+) Tregs express eGFP and diphtheria toxin (DT) receptor. In this model, specific and transient Tregs depletion is achieved by DT administration. Using this model, we evaluated the effect of Tregs depletion on the immunogenicity of an experimental recombinant vaccine against the pathogenic fungus Sporothrix shenckii. Tregs depletion enhanced the frequency of specific IFNγ+ Tregs and cytokine production during either the first or second vaccine dose. However, depletion of Tregs during the second dose caused greater stimulation than during the first dose. A similar result was observed in the production of specific antibodies where the highest production of IgG, IgG1, and IgG2a anti rSsEno was detected after depletion of Tregs during boost immunization compared to the other immunized groups. Importantly, vaccine immunogenicity improvement after Tregs depletion also had an impact on the more efficient reduction of fungal load in the skin and liver after the challenge with S. schenckii in an experimental infection model. Interestingly, the reduction in fungal load was greatest in the Tregs depleted group during boosting. Collectively, our results demonstrate that a specific and transient depletion of Tregs could enhance the rSsEno vaccine-induced immune response and potentially improve vaccine efficacy.